FORMULASI SABUN PEMBERSIH KEWANITAAN (Feminime Hygiene) DARI MINYAK ATSIRI RIMPANG LENGKUAS PUTIH (Alpinia galanga L) DAN UJI AKTIFITAS ANTISEPTIK TERHADAP Candida albicans - Wida Ningsih; Diana Agustin; Putri Sefrianti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACTCandida albicans is a normal flora in the female genitalia which can cause vaginal discharge. White galangal rhizome contains essential oils of eugenol which have activities that inhibit the growth of Candida albicans. This study formulated the white galangal rhizome essential oil in the form of feminime hygiene to make it easier and more comfortable to use and to determine the antiseptic feminime hygiene activity of the white galangal rhizome oil of Candida albicans. The essential oil of white galangal rhizome is formulated in three variations of concentration namely 10%, 15% and 20%. Feminime hygiene of essential white galangal rhizome oil was evaluated such as organoleptic, homogeneity, specific gravity, foam power test, viscosity, pH and stability. Antiseptic activity testing was tested with SDA (Sabouraud Dextrose Agar) media and using agar diffusion method. The results of the feminime hygiene evaluation formulated showed results similar to the results of comparative evaluations (BN). The parameters of antiseptic activity are indicated by the formation of inhibitory zone diameters where F0 (negative control), F1 (10%), F2 (15%), and F3 (20%) respectively have an average diameter value of 11 mm, 14.65 mm 17.58 mm and 25.41 mm. The classification category of the response to microbial growth according to CLSI, F0 and F1 includes the weak group, the F2 is the moderate group and the F3 is the strong group. Based on the results of one-way ANOVA statistical analysis there were significant differences in liquid soap preparations F0, F1, F2 with F3 at (P <0.05). White galangal rhizome essential oil can be formulated into feminine hygiene and has antiseptic activity against the fungus Candida albicans.Keywords: white galangal, antiseptic, candida albicans